Duration of initial prednisolone therapy for first episode of childhood nephrotic syndrome based on time to response - Tang, Xiaoshan; Shen, Qian; Rao, Jia; Chen, Jing; Fang, Xiaoyan; Zhang, Zhiqing; Grewal, Manpreet; Mattoo, Tej; Xu, Hong (Frontiers in Pediatrics, 2022)
Background: The duration of initial corticosteroid therapy in newly diagnosed Idiopathic nephrotic syndrome (INS) is about 3 months. Our study was designed to test the feasibility of a shorter duration of corticosteroid therapy in newly diagnosed INS who show a quicker response. Methods: Patients who responded within 10 days (Group A) received 8 weeks of corticosteroid therapy as compared to 12-14 weeks of standard therapy in those who responded between >10 days to 28 days (Group B)，and follow up for 52 weeks. The primary endpoint is time to first relapse after treatment completion. (NCT03878914, March 18, 2019) Results: A total of 33 children with INS were enrolled and the follow-up data were analyzed. The clinical and laboratory characteristics of patients in both groups were similar. No significant diﬀerence was found in time to first relapse [65(14.5, 159) days for Group A vs 28(17, 61.5) days for Group B, P=0.371], the incidence of frequently relapsing nephrotic syndrome [6/18 (33.3%) vs 5/10(50%), P=0.644] or requirement for alternative immunosuppressant [4/18 (22.2%) vs 1/10 (10%), P=0.769]. Group A received similar corticosteroid dose compare with Group B (3511±2421 mg/m2 versus 4117±2556 mg/m2, P=0.524). Frequency and severity of corticosteroid-related complications was similar in both groups. Conclusions: The time to first relapse and the number of relapses per patient were comparable between the two groups. However, more patients in Group A relapsed and the mean total dose of prednisolone for the study period was very similar between the two groups.